A minimum-disruption approach to input–output disaster analysis. Issue 4 (2nd October 2022) - Li, Mengyu; Lenzen, Manfred; Pedauga, Luis E.; Malik, Arunima
ABSTRACT: The frequency of disasters has been increasing over the past decades, fuelled by natural phenomena and climate-related events. Policymakers require robust methodologies to assess supply-chain impacts of disasters. Input–output-based disaster approaches are able to assess such impacts; however, they rely on some assumptions, such as the fixed production-recipe assumption for industries or the possibility of negative final demand. This study presents an improved disaster analysis approach, called minimum disruption, in order to assess more realistically the impacts of a disaster on essential and non-essential sectors. In particular, we propose a priority-weighted approach for incorporating decision-makers' priorities for transitioning economies to post-disaster equilibrium. We showcase the new approach by modelling the actual occurrences during Venezuela's economic crises.